INVESTIGATING THE IMPACT OF COVID-19 ON LOSS OF SMELL (ANOSMIA) AND TASTE (AGEUSIA): A COMPREHENSIVE REVIEW - Bala, Jyoti; Sharma, Sanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The loss of smell (anosmia) and taste (ageusia) has emerged as a distinctive symptom associated with COVID-19 infection. This paper provides an extensive review of existing literature on the prevalence, mechanisms, clinical implications, and management of anosmia and ageusia in COVID-19 patients. The sudden onset of these sensory deficits has significant implications for diagnosis, patient management, and public health strategies. By synthesizing findings from epidemiological studies, clinical reports, and mechanistic investigations, this review aims to deepen our understanding of the pathophysiology underlying COVID-19-related anosmia and ageusia and inform strategies for diagnosis, treatment, and prevention.